Slovenija in slovenski motivi v Koledarju SPKD Prosvjeta (1905–1947) - Babić, Biljana (Dve domovini, 2025)
During Austro-Hungarian rule—and later in the first unified South Slavic state—periodical publications in Bosnia and Herzegovina served as a popular means for enlightening all strata of the population. One of those publications, the Calendar of the Serbian Educational and Cultural Society (SPKD) Prosvjeta, featured a variety of texts, ranging from literary contributions to expert articles on health, agriculture, geography, pedagogy, and other topics. These texts served as testimonies not only about the Serbian community but also about others. The study analyzes the headlines and news related to Slovenia and Slovenian motifs published in the Calendar between 1905 and 1947.
Keywords: calendars; emigrant associations; izseljenska društva; koledarji; periodicals; periodika; Slovenia; Slovenian emigrants; Slovenian motifs; Slovenija; slovenski izseljenci; slovenski motivi